P‐199: Novel Electron Transporting Materials for Long Lifetime Fluorescent Blue OLED Devices and Lighting Applications. Issue 1 (2nd June 2017) - Huang, Heh-Lung; Guo, Huang-Ming; Yao, Cheng-Chung; Lin, Chi-Jen
Abstract : A series of new electron transporting materials with good thermal stability were designed and developed. The devices of these ETs applied in fluorescent blue devices, exhibited high efficiency and long lifetime with efficiency of 9.3‐10.4 cd/A and the LT95 lifetime is around 250‐1000 h under 1000 cd/m2.